Piloting the Describing and Evaluating community Pharmacy practice to Improve patients' Care and Treatment tool. (23rd March 2020) - Chevalier, Bernadette; Cottrell, William N; Hegerty, Tobias; Morgan, Ashleigh; Freeman, Christopher
Abstract: Objective: To pilot the Describing and Evaluating community Pharmacy practice to Improve patients' Care and Treatment (DEPICT) tool to determine its utility in collecting data about Australian community pharmacist activities and patient-related encounters. Methods: DEPICT tool was developed and tested. Two pharmacy students recruited study patients and collected data in four urban pharmacies. Key findings: Fourteen pharmacists completed 189 DEPICT forms. Pharmacists' evaluations indicated overall high levels of satisfaction and provided valuable recommendations for improvement. Conclusions: Pharmacists' feedback will be incorporated into future iterations of DEPICT that will include electronic collection of regional data in urban and rural settings.